Computer-assisted telephone interviewing (CATI): using the telephone for obtaining information on reproductive health Computer-assisted Telephone Interviewing (CATI): usando telefone para a obtenção de informações sobre saúde reprodutiva - Jose Guilherme Cecatti; Rodrigo P. S. Camargo; Rodolfo Carvalho Pacagnella; Thaís Giavarotti; João Paulo Souza; Mary Angela Parpinelli; Maria José Duarte Osis (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The objective of this study was to evaluate the feasibility of using computer assisted telephone interviewing (CATI) as a method for obtaining information on reproductive health in Brazil. A total of 998 eligible women for the study were selected to answer a questionnaire through computer- assisted telephone interviewing undertaken by trained interviewers. The outcomes of each telephone contact attempt were described. Differences between groups were assessed using the χ2 test. Phone contact was made in 60.3% of the attempts and 57.5% of the interviews were completed. The success rate improved with the decrease in time from hospitalization to interview and with the higher numbers of telephones available. A total of 2,170 calls were made, comprising of one to sixteen attempts per woman. The majority of situations where extra calls were necessary were due to the number being busy or to the fact that the woman was not available at the time of the call. CATI can prove be a valuable procedure for obtaining information on reproductive health among Brazilian women, particularly for relatively recent events and when more than one alternative telephone number is available. O objetivo foi avaliar a facticidade do telefone como um método de obtenção de informações sobre saúde reprodutiva no Brasil (CATI). Um total de 998 mulheres elegíveis a um estudo foi selecionado para responder um questionário por telefone com o auxílio de computador e aplicado por entrevistadoras treinadas. Os resultados de cada tentativa de contato estão descritos. A diferença entre os grupos foi avaliada pelo teste qui-quadrado. O contato telefônico foi feito em 60,3% e 57,5% completaram a entrevista. A taxa de sucesso melhorou com a diminuição do tempo entre a hospitalização e a entrevista e com a quantidade de números de telefone disponível. Um total de 2.170 chamadas foi feito, de 1 a 16 tentativas por mulher. A maioria das chamadas adicionais foi em razão de a linha estar ocupada ou de a mulher não ter disponibilidade naquele momento. O CATI pode ser um procedimento útil para obtenção de informações em saúde reprodutiva entre mulheres brasileiras, especialmente se dirigido a eventos relativamente recentes e quando mais de um número alternativo de telefone está disponível.